白令海北部陆坡全新世以来的生物标志物记录及其古环境意义 - 张海峰; 王汝建; 陈荣华; 高爱国; 李丽; 王慧 (2014)
通过白令海北部陆坡区b2-9站位沉积物柱样高分辨率的生物标志物(菜子甾醇、甲藻甾醇、长链烯酮、n-C30-dIOl)提取和分析,获得了近1万年来浮游植物群落和初级生产力、高碳烷烃输入与陆源植被变化等相关记录,研究结果显示,全新世以来表层浮游植物和初级生产力都经历了“高-低-高“的变化过程,并具有明显的阶段性,可能受控于陆架坡折处海冰的分布、上层海洋营养盐供应和全新世气候与环境的变迁;浮游植物群落结构较为稳定,硅藻是初级生产力的主要贡献者,甲藻次之,颗石藻和黄绿藻比前两者低了1个数量级,硅藻与甲藻之间具有明显的竞争关系,前者明显占据优势,是白令海有机碳汇的主要贡献者;正构烷烃总量分别在7.8 kA bP,6.7 kA bP和5.4 kA bP,经历了3次阶梯状的下降过程,并呈现出4个相对稳定的阶段,其主要受控于早全新世海平面上升以及周边陆地植被源区的气候与环境变化;正构烷烃分子组合特征显示其来自陆地高等植物、且陆源植被结构较为稳定,木本植物占据优势;单体碳同位素研究表明正构烷烃的主碳峰为n-C27,对烷烃总量的贡献最大,可能与当时陆源繁盛的木本植物及输入有关,含量较高的n-C23则可能主要来源于北半球沿海广泛分布的一类沉水植物。 Variations in phytoplankton community and primary productivity,plus input of terrestrial high-carbon nalkanes and vegetation changes in their source during the last 9.6 ka are investigated based on extraction and measurement of high-resolution biomarkers(brassicasterol,dinosterol,n-C37-alkenone,n-C30-diol) at Site B2-9 on the northern Bering Sea Slope.The results show that surface phytoplankton and primary productivity have undergone obvious periodic changes from high to low and back to high during the Holocene,which might have been controlled by sea-ice expansion on the shelf-break,nutrient supplementation at the sea surface,and climate change.Diatoms were the greatest contributors to primary productivity,followed in turn by dinoflagellates,coccolithophores and eustigmatophytes.The abundance of eustigmatophytes was an order of magnitude lower than those of dinoflagellates and coccolithophores in the steady phytoplankton community.In the clear competitive relationship between diatoms and dinoflagellates,the former had an obvious advantage,and formed the major input to organic carbon sinks in the Bering Sea.Furthermore,the stepwise total n-alkanes dropped quickly at 7.8 ka BP,6.7 ka BP and 5.4 ka BP, indicating that there were four relatively stable stages,which might have been controlled by sea-level rise during the early Holocene and environmental changes in the terrestrial vegetation source surrounding the Bering Sea.The molecular parameters indicate that the n-alkanes originated from terrestrial higher plants with a stable vegetation structure,and woody plants dominated in this type of assemblage.Mono-carbon isotopic results show that the n-C27content was the main carbon peak and dominated the total n-alkanes,which might be related to the abundance of woody plants in the vegetation source and their spatial distribution.The higher n-C23content may have been mainly derived from submerged plants,which are widely distributed along coastal areas in the northern hemisphere. 国家自然科学基金重点项目(41030859)、国家自然科学基金中俄合作与交流项目(41211120173); 南北极环境综合考察与评估专项(CHINARE2013-03-02;CHINARE2013-04-01); 国家海洋局极地考察办公室对外合作支持项目(IC201105); 中国地质调查局地质调查工作项目(水[2013]02-013-012)资助